Réponses

2014-09-06T14:15:56+02:00
Bonjour


(-x²)/2+6x=9
(-1/2)x² +6x - 9 = 0

calculons Δ
Δ = b² - 4ac = (6)² - 4(-1/2)(-9)
Δ = 36 -18 = 18
Δ = 18  et √18 = 3√2

x1 = (-b - √Δ) / 2a
x1 = (-6 - 3√2) / -1
x1 = 6 + 3√2

x2 = (-b + √Δ) / 2a
x2 = (-6 + 3√2) / -1
x2 = 6 - 3√2

S =  {6 + 3√2; 6 - 3√2}


(-x²)/2+6x=18
(-1/2)x² + 6x - 18 = 0

Calculons Δ

Δ = b² - 4ac = (-6)² - 4(-1/2)(-18) = 36 - 36
Δ = 0

donc nous avons une seule racine double
x1 = x2 = -b/2a = (-6) / (2 x (-1/2)) = -6 / -1 = 6
x1 = x2 = 6
S = {6}